2023
DOI: 10.1021/acs.est.3c00374
|View full text |Cite
|
Sign up to set email alerts
|

Legacy and Emerging Per- and Polyfluoroalkyl Substances in a Subtropical Marine Food Web: Suspect Screening, Isomer Profile, and Identification of Analytical Interference

Abstract: The ban/elimination of legacy per- and polyfluoroalkyl substances (PFASs) has led to a dramatic increase in the production and use of various emerging PFASs over the past decade. However, trophodynamics of many emerging PFASs in aquatic food webs remain poorly understood. In this study, samples of seawaters and marine organisms including 15 fish species, 21 crustacean species, and two cetacean species were collected from the northern South China Sea (SCS) to investigate the trophic biomagnification potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…At least four processes may be involved: (1) biomagnification by predation on terrestrial organisms; (2) biomagnification by predation on aquatic organisms; (3) inhalation exposure on land (including direct and indirect sources, i.e., degradation of gaseous precursors); and (4) bioconcentration by dermal exposure in water. With the increase in carbon chain length, the raised n -octanol/water partition coefficient (log K OW ) of PFAAs could promote their accumulation through pathways 1, 2, and 4, which is consistent with previous laboratory experiments and field-based investigations on aquatic organisms. , Nevertheless, for PFCAs with more than eleven perfluorocarbons, a decreasing trend was found between BAF and carbon chain length, which is also observed in previous studies, and the most possible reason is the relatively large molecular size could inhibit the bioaccumulation of PFCAs with perfluorocarbon chain longer larger than eleven. , Notably, the BAF of two short-chain PFCAs, PFPeA and PFHxA, exhibited higher BAF (1.77 and 1.82, respectively) compared to PFOA (1.27). This result indicated the high bioaccumulation potential of the short-chain PFCAs in the Chinese toads, and the bioaccumulation potential of PFPeA and PFHxA is even higher than the C7 compound.…”
Section: Resultssupporting
confidence: 90%
“…At least four processes may be involved: (1) biomagnification by predation on terrestrial organisms; (2) biomagnification by predation on aquatic organisms; (3) inhalation exposure on land (including direct and indirect sources, i.e., degradation of gaseous precursors); and (4) bioconcentration by dermal exposure in water. With the increase in carbon chain length, the raised n -octanol/water partition coefficient (log K OW ) of PFAAs could promote their accumulation through pathways 1, 2, and 4, which is consistent with previous laboratory experiments and field-based investigations on aquatic organisms. , Nevertheless, for PFCAs with more than eleven perfluorocarbons, a decreasing trend was found between BAF and carbon chain length, which is also observed in previous studies, and the most possible reason is the relatively large molecular size could inhibit the bioaccumulation of PFCAs with perfluorocarbon chain longer larger than eleven. , Notably, the BAF of two short-chain PFCAs, PFPeA and PFHxA, exhibited higher BAF (1.77 and 1.82, respectively) compared to PFOA (1.27). This result indicated the high bioaccumulation potential of the short-chain PFCAs in the Chinese toads, and the bioaccumulation potential of PFPeA and PFHxA is even higher than the C7 compound.…”
Section: Resultssupporting
confidence: 90%
“…3 Bis-FMeSI (bis-(trifluoromethylsulfonyl)imide; [C 2 F 6 NO 4 S 2 ] − ) was tentatively identified primarily in Nova Scotia samples and was also previously detected by Wang et al in seawater from the South China Sea. 33 However, Wang et al did not detect bis-FMeSI in marine biota via analysis of the whole body (crustaceans and fish) and liver tissue (mammals). Our detections of potential novel compounds in white shark plasma and their geographical distinctions could be linked to differences in diet, metabolism, and gill respiration, and the data highlight the need for further detailed analyses.…”
Section: Additional Pfass Detected In Plasma Via Hrms Suspect Screeningmentioning
confidence: 99%
“…Along with legacy PFAAs like the PFCAs and PFSAs, novel PFASs have been detected in marine biota using high-resolution mass spectrometry (HRMS) techniques. ,, A recent study observed significant contributions from unidentified organofluorine (30–75% of extractable organofluorine) in marine organisms in the Northwest Atlantic Ocean and identified 37 additional PFASs from 12 subclasses in tissue samples via HRMS suspect screening . HRMS suspect screening and nontarget analysis also led to the tentative identification of 54 PFASs in nine different subclasses in the livers of beluga whales from the St. Lawrence Estuary and 44 PFASs from nine different subclasses in livers collected from cetaceans in the South China Sea . Among these studies, ether-substituted PFSAs and PFCAs (PFESAs and PFECAs), , unsaturated/cyclic PFSAs, ,, hydrogen-substituted PFAAs and PFESAs, , perfluoroalkyl sulfonamides (FASAs), ,, and x :3 fluorotelomer carboxylates ( x :3 FTCAs) ,, were tentatively identified with varying levels of confidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HFIP and NTf2 were reported for the first time in the soil environment. So far, through the combination of different screening strategies, the identification of novel PFAS in the environment can be achieved accurately and efficiently. ,, Nevertheless, with the TOP assay embedded in the strategy of nontarget analysis, not only novel PFAS can be identified but also their potential roles in the environmental processes can be predicted. Previously, novel products such as HPFCAs, UPFECAs, and perfluoroalkyl diacids were identified as possible transformation products of other PFAS. , However, the identification of potential transformable precursors, especially those weakly ionized and semivolatile PFAS, are challenging due to their low deprotonation capability in electrospray-ionization-based MS/MS analysis.…”
Section: Environmental Implicationsmentioning
confidence: 99%